2012
DOI: 10.3390/ijms130810067
|View full text |Cite
|
Sign up to set email alerts
|

2,3-Dihydro-1H-cyclopenta[b]quinoline Derivatives as Acetylcholinesterase Inhibitors—Synthesis, Radiolabeling and Biodistribution

Abstract: In the present study we describe the synthesis and biological assessment of new tacrine analogs in the course of inhibition of acetylcholinesterase. The obtained molecules were synthesized in a condensation reaction between activated 6-BOC-hydrazinopyridine-3-carboxylic acid and 8-aminoalkyl derivatives of 2,3-dihydro-1H-cyclopenta[b]quinoline. Activities of the newly synthesized compounds were estimated by means of Ellman’s method. Compound 6h (IC50 = 3.65 nM) was found to be most active. All obtained novel c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…However, it was more selective towards BChE (IC 50 = 0.0354 nM) over AChE [40]. Among the analogs 8 ( Figure 4, Table 1) reported as hybrids of tacrine and hydrazine nicotinate moiety by the same research group [41,42], the analog 8a was weaker eeAChE inhibitor (IC 50 = 308 nM) than the reference tacrine (IC 50 = 5.46 nM) and was selective towards esBChE (IC 50 = 0.65 nM) [41]. The other analog 8b, with longer alkyl spacer and smaller size of tricyclic ring compared to 8a, was stronger AChEI (IC 50 = 3.65 nM) than tacrine (IC 50 = 5.46 nM) with 4685 times selectivity towards AChE over BChE (IC 50 = 17100 nM) [42].…”
Section: Tacrine Analogsmentioning
confidence: 96%
“…However, it was more selective towards BChE (IC 50 = 0.0354 nM) over AChE [40]. Among the analogs 8 ( Figure 4, Table 1) reported as hybrids of tacrine and hydrazine nicotinate moiety by the same research group [41,42], the analog 8a was weaker eeAChE inhibitor (IC 50 = 308 nM) than the reference tacrine (IC 50 = 5.46 nM) and was selective towards esBChE (IC 50 = 0.65 nM) [41]. The other analog 8b, with longer alkyl spacer and smaller size of tricyclic ring compared to 8a, was stronger AChEI (IC 50 = 3.65 nM) than tacrine (IC 50 = 5.46 nM) with 4685 times selectivity towards AChE over BChE (IC 50 = 17100 nM) [42].…”
Section: Tacrine Analogsmentioning
confidence: 96%
“…The final hydrochlorides, derivatives 19a–h , were obtained through crystallization from HCl in ether (Figure ). Quinoline compounds 21a–h were obtained by Szymański, Lázničková, Lázniček, et al () using the same method described above for tacrine analogs 19a–h (Figure ).…”
Section: Synthetic Modes Of Tacrine Derivativesmentioning
confidence: 99%
“…Synthesis of tacrine–hydrazinonicotinamide hybrids 19a–h , 8‐amino‐2,3‐dihydro‐1H‐cyclopenta[b]quinolones 20a–h and 6‐Hydrazino‐ N ‐[2‐(2,3‐dihydro‐1H‐cyclopenta[b] quinolin‐9‐ylamino)alkyl]nicotinamide hydrochlorides 21a–h (Szymański et al, ; Szymański, Markowicz, & Mikiciuk‐Olasik, ; Szymański, Lázničková, Lázniček, et al, )…”
Section: Synthetic Modes Of Tacrine Derivativesmentioning
confidence: 99%
“…Studies on biodistribution of tetrahydroacridine derivatives with similar structure showed that these compounds accumulate mainly in the rat's lungs and intestines [30]. A series of novel tetrahydroacridine and cyclopentaquinoline derivatives with fluorobenzoic acid moieties were synthesized and evaluated for their anticancer properties by our research team previously [13,31].…”
Section: Introductionmentioning
confidence: 99%